Village Baseline Study: Site Analysis Report for Chicualacuala, Maluana, Mozambique (MO0145) - Onyango, Leah; Raimundo Finiasse, A; Mango, Joash; Wamubeyi, B.; Loo, L; Guambe, D; Michaque Manhique, H; Dixon, R. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
This is the report of the village baseline study of Maluana village in the CCAFS benchmark site of Chicualacuala, Mozambique from May 5-12, 2013 to complement an earlier household baseline survey done in the same village.